Prototype Smart Alarm Automated System Berbasis DFPlayer Mini Untuk Mengefisiensikan Jadwal Waktu - Indah Khairunnisa Ahmad Hutasuhut (LPPM STMIK ANTAR BANGSA, 2023)
Prototype is a basic concept of a design that can be developed periodically, can be defined as an original model, or an example that can be developed into the next process for a better design process. Currently, technology is developing well and making some local people change their habits in their activities. For example, activities that are usually done manually can now be done automatically. There is a difference, namely habits in terms of time. For example, reminders at school or school bells, which are usually done manually by pressing the instruction button at certain hours, to inform students to go to the next lesson, entrance bell, rest, and reminder bell information lesson hours have ended. The author makes a Prototype Smart Alarm Automated System as a smart reminder of an efficient schedule automatically for people, especially those in the school environment. Making this prototype is one of the first steps to train students at school to understand a time that has entered and be disciplined in time.